Integrasi Konteks Jembatan Suramadu dalam E-Modul Matematika Berbasis Deep Learning pada Materi Skala dan Perbandingan - Nur Halimatus Sa'diyah; Ani Afifah; Keto Susanto (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
This research aims to develop a deep learning-based mathematics e-module with the integration of the context of the Suramadu Bridge in scale and comparison materials for grade VII junior high school students. The development model used is the 4D (Define, Design, Develop, Disseminate) model which includes the stage of defining learning needs, designing e-modules, product development, and limited deployment. The research instruments used included validation sheets of media and material experts, observation sheets of teacher and student activities, learning outcome tests, and student response questionnaires. The results of the study showed that the e-modules developed met the valid criteria with a media validity level of 94.29% and material of 95%. In addition, the e-module is considered practical with teacher practicality of 78.67% and students of 86.67%, and effective with a learning effectiveness rate of 83.83%. The students' response to the e-module was also very positive, which showed that the integration of the local context of the Suramadu Bridge and the deep learning approach was able to increase student engagement, learning motivation, and understanding of mathematical concepts in a meaningful way. These findings indicate that local context-based e-modules can be an innovative alternative in mathematics learning that is relevant to students' real lives as well as support the implementation of 21st century learning.